To Sink or Swim: Evaluating Coastal Archaeological Stability through a System of Indices. (1st November 2020) - Jones, Jennifer E.; Allen, Mary E.; Loomis, David K.
ABSTRACT: Archaeological resources in the coastal zone are subjected to a variety of cultural, social, and environmental conditions that affect a site's stability, which can be defined in physical (e.g. structure, geophysical environment), sociocultural (e.g. looting, vandalism), and regulatory (e.g. federal, state, and local mandates) terms. To effectively manage resources within this dynamic environment requires a holistic understanding of what drives stability (or instability) at each site. The systematic development of indices for archaeological site stability aggregates a large number of complex conditions, both drivers and pressures, into a smaller set of key indicators that can be used to evaluate site stability, and to monitor changes over time. This system of indices provides an integrated framework for evaluation of site-specific stability that allows for adaptive management and the prioritisation of resources (e.g. funding, time, staff).